Shading Responses of the Seagrass Halophila Ovalis (R. Br.) Hook. F. From Teluk Kemang, Negri Sembilan, Malaysia - Jamaludin, Mohammad Rozaimi (2008)
The seagrass Halophila ovalis from Teluk Kemang coast (2 ° 30'N, 101 ° 45'E) in Port Dickson, Negeri Sembilan was studied to elucidate its responses towards artificial shading. Responses were firstly based on autotrophic productivity of H. ovalis through photosynthesis experiments to determine the effects of prior acclimation to the condition of either in the field (naturally growing) or in cultures (light reduced to 85-90% of ambient conditions). Results showed that the light compensation values in field and cultured leaves (8-13 μmol m-2 s-1) were similar while saturation point was in the range of 268-275 μmol m-2 s-1 for field leaves and increased to 290-293 μmol m-2 s-1 for cultured leaves. A one-month long artificially imposed shading was then performed to plants in the field (50%, 65%, 80% and 95% shading relative to field light intensity) and in cultures (92% shading – Tank 1, and 96% shading – Tank 2, relative to field light intensity) and compared to unshaded plants as a control showed the following responses. Photosynthetic rates of field H. ovalis at two tide levels as determined using the Biological Oxygen Demand bottle method was up to six times higher when compared to the oxygen electrode method. Leaf chlorophyll content was significantly higher from plants under shading for both field and cultured leaves compared to control where leaves from cultures (Tank 2) showed the highest value in leaf chlorophyll content (1353.40 + 74.00 μg chlorophyll a g-1, p < 0.01, and 11.92 + 0.59 μg chlorophyll a cm-2, p < 0.01, by leaf fresh weight and leaf surface area respectively, and 744.30 + 46.55 chlorophyll b g-1 , p < 0.01 and 6.56 + 0.39 μg chlorophyll b cm-2 , p < 0.01, by leaf fresh weight and leaf surface area respectively). For carbohydrates, starch and the reducing sugars of glucose, sucrose, fructose and maltose were tested for in the below-ground portions of field plants, and above-ground and belowground portions of cultured plants. Starch was not detected in both aboveground and below-ground plant portions of both field and culture studies. Glucose content was highest among the four sugars, in both field and culture plants but not significantly different compared to the control. Changes in growth rates were the most discernible where increased shading results in decreased growth rates (3.72 + 0.51 mm apex-1 day-1 from control plants, to the significantly lowest recorded growth rate value of 0.746 + 0.205 mm apex-1 day-1, p < 0.01, from Tank 1 plants). Leaf morphology based on leaf length, leaf width, leaf petiole length, number of cross veins per leaf, leaf fresh weight and leaf surface area were significantly higher for leaves under shading in culture condition compared to field-shaded leaves and the control. This is substantiated by the data from Tank 2 where leaf length is 24.73 + 0.54 mm, leaf width – 9.38 + 0.23, leaf length-width ratio – 2.80 + 0.030, leaf petiole length – 28.48 + 1.03, leaf cross vein number – 14.47 + 0.27, leaf fresh weight – 0.0179 + 0.00134 and leaf surface area – 2.011 + 0.126) compared to the unshaded control (leaf length: 13.20 + 0.54 mm; leaf width: 6.81 + 0.29; leaf length-width ratio: 1.93 + 0.037; leaf petiole length: 11.20 + 1.43; leaf cross vein number: 11.40 + 0.35; leaf fresh weight: 0.00680 + 0.000548; and leaf surface area: 0.796 + 0.0744). For field biomass values, there were no significant differences between shaded plants and the control. Comparatively, culture biomass values of Tank 1 were significantly higher for both above-ground biomass (0.0127 + 0.00238 g DW rhizome-1, p < 0.01) and below-ground biomass (0.0282 + 0.00245 g DW rhizome-1, p < 0.01) compared to the unshaded control (0.0107 + 0.000914 g DW rhizome-1 and 0.0192 + 0.00109 g DW rhizome-1 for above-ground and below-ground biomass respectively). All the observations and results collated showed H. ovalis tolerates extreme low light conditions as low as 96% shading (80 μmol m-2 s-1) by modifying its various physical and biochemical characteristics accordingly with its light environment. This is also evident that the plant survives and continues to maintain productivity with respect to photosynthesis and carbohydrate production even under the highest shading levels imposed in both field (95% shading) and cultures (Tank 2 – 96% shading). Furthermore, it is possible to culture H. ovalis, although maximum growth densities equivalent to those observed in the field were not achieved. The findings suggest that lowered light availability may not be the sole causal factor for H. ovalis loss in a particular area. Other aspects such as epiphytic fouling and available nutrients could be more important in the loss of H. ovalis vegetation, although an interaction of the factor of reduced light and these other factors should not be discounted.